Morphological Response of Several Rice Varieties to Drought Stress Simulation using PEG - Rezi Nabilah; Afifatul Achyar; Zulyusri Zulyusri; Yusni Atifah; Dwi Hilda Putri; Violita Violita (Bioscience, 2024)
Rice has become food for most of the world's population. Indonesia is the third largest producer in the world. However, in fact rice production in Indonesia has decreased by 0.43% compared to 2020. One of the factors that can cause this decline is drought. Because rice is a semi-aquatic plant that grows normally in flooded conditions, it makes drought stress very threatening. Drought stress that occurs in plants causes plants to experience oxidative stress due to excessive accumulation of ROS. PEG is a compound that is widely used to provide drought conditions in plants. Previous research has classified several varieties of rice plants based on their level of resistance to drought. However, it is not yet known how the morphological response will be in different periods of drought stress and rewatering treatment. This research was conducted by giving treatment in the form of control (Yoshida nutrient culture solution) and drought stress (Yoshida + PEG-6000 20% solution) repeated 3 times. The observed parameters were RWC which were analyzed using standard errors and morphological images of roots and leaves. The results showed that the RWC obtained during the stress period from the third to the fifth day, Harum had the highest value according to its class as tolerant rice. After rewatering Rosna has a better recovery ability. In addition, root morphology shows differences in the form of root length, small root diameter, inhibition of adventive root growth. On the leaves include a decrease in leaf area, leaf curl up, and leaf yellowing.